Cover Jurnal Fitopatologi Vol. 18 No. 3, Mei 2022 - Editors (Jurnal Fitopatologi Indonesia, 2022)
This editorial contains the front cover, editorial page, and back cover of the Jurnal Fitopatologi Indonesia Vol. 18 No. 3, Mei 2022